REASONABLE TREATMENT OF ADOLESCENTS WITH L-CARNITINE AND COENZYME Q10 - S.O. Klyuchnikov; D.A. Il'yashenko; M.S. Klyuchnikov ("Paediatrician" Publishers LLC, 2008)
Advisability of clinical use of l-carnitine (Karniton) and coenzyme q10 (qudesan) in adolescents is discussed in this article. An evidence of activity of these medications were based on analysis of results of clinical, functional (cardiointervalography), cytochemical investigation and special psychological testing. Combined treatment with both medications has a beneficial effect for the increase of adaptative resources of adolescents. Key words: adolescents, coenzyme q10, carnitine, psychological testing, adaptation.